Predictors of Transfer to Home Hemodialysis after Peritoneal Dialysis Completion. Issue 5 (September 2016) - Nadeau-Fredette, Annie-Claire; Hawley, Carmel; Pascoe, Elaine; Chan, Christopher T.; Leblanc, Martine; Clayton, Philip A.; Polkinghorne, Kevan R.; Boudville, Neil; Johnson, David W.
Background: The aim of the present study was to evaluate the predictors of transfer to home hemodialysis (HHD) after peritoneal dialysis (PD) completion. Methods: All Australian and New Zealand patients treated with PD on day 90 after initiation of renal replacement therapy between 2000 and 2012 were included. Completion of PD was defined by death, transplantation, or hemodialysis (HD) for 180 days or more. Patients were categorized as "transferred to HHD" if they initiated HHD fewer than 180 days after PD had ended. Multivariable logistic regression was used to evaluate predictors of transfer to HHD in a restricted cohort experiencing PD technique failure; a competing-risks analysis was used in the unrestricted cohort. Results: Of 10 710 incident PD patients, 3752 died, 1549 underwent transplantation, and 2915 transferred to HD, among whom 156 (5.4%) started HHD. The positive predictors of transfer to HHD in the restricted cohort were male sex [odds ratio (OR): 2.81], obesity (OR: 2.20), and PD therapy duration (OR: 1.10 per year). Negative predictors included age (OR: 0.95 per year), infectious cause of technique failure (OR: 0.48), underweight (OR: 0.50), kidney disease resulting from hypertension (OR: 0.38) or diabetes (OR: 0.32), race being Maori (OR: 0.65) or Aboriginal and Torres Strait Islander (OR: 0.30). Comparable results were obtained with a competing-risks model. Conclusions: Transfer to HHD after completion of PD is rare and predicted by patient characteristics at baseline and at the time of PD end. Transition to HHD should be considered more often in patients using PD, especially when they fulfill the identified characteristics.